PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS PROSEDUR - Zuan Andrea Cevin Sitepu; Liana Siburian; Jesika Simorangkir; Fanny Wijayanti Sihombing; Lastri Situmorang; Ronaida Raimunda Simbolon (LPPM Universitas Cipta Mandiri, 2026)
This study focuses on the development of visual-based interactive learning media to strengthen the skills of junior high school students in writing procedural texts. (SMP). The basis of this scientific review is the low writing skills of students due to the use of traditional and less interactive teaching tools. This study applies the Research and Development (R&D) method with the ADDIE design, which includes the steps of Analysis, Design, Development, Implementation, and Evaluation. The subjects who played a role in this study were seventh-grade junior high school students. Data were collected through a test of proficiency in composing procedural texts given before and after the use of educational tools. The results of the data analysis indicate a significant increase in students' writing skills. The average student score increased from 61.81 in the pretest to 84.47 in the posttest, with the results of the paired samples t-test showing a significance value of 0.000 <0.05. These results indicate that the use of image-based interactive learning tools is effective in improving the ability to write procedural texts. Therefore, this media is worthy of being used as an innovative and relevant choice in Indonesian language learning based on the Independent Curriculum and the Deep Learning approach.